Celiac Disease: Comparison of Oberhuber Classification and Corazza- Villanacci Classification - Ghanghoria, Shikha; Sharma, Sachin; Jain, Priya (Annals of Pathology and Laboratory Medicine, 2019)
Background: Celiac disease occurs in genetically predisposed individuals on consumption of certain grains. The diagnosis is based on biopsy showing the presence of characteristic histological changes in duodenum and jejunum that improve after gluten free diet. The Oberhuber Classification is very widely used by pathologists. The new Corazza-Villanacci Classification simplifies the criteria. Methods: Retrospectively diagnosed 200 patients of Celiac disease according to Oberhuber classification over duration of 05 years were considered. The 200 cases were retrieved from the records and were sent to two pathologists, who were blinded to each other and were not given any clinical information. Each pathologist received the set of biopsy specimens on two separate occasions and had reclassified them according to both grading systems in a random order. The interobserver variation was then determined after re-examination according to Oberhuber classification and after using to Corazza-Villanacci classification too Result: Mean kappa values were 0.77 (good) for the Oberhuber classification versus 0.98 (very good) for the Corazza -Villanacci classification Conclusion: The Corazza-Villanacci classification gives better interobserver agreement compared with the Oberhuber classification and contributes to the validity of diagnosis in celiac disease.